2015
DOI: 10.1590/s1678-86212015000300026
|View full text |Cite
|
Sign up to set email alerts
|

Influência do uso de aditivo retentor de água à base de éter de celulose nas propriedades das argamassas de assentamento em alvenaria estrutural de blocos de concreto

Abstract: Resumoobjetivo deste trabalho foi estudar a influência do uso de aditivo retentor de água à base de éter de celulose em argamassa de assentamento para alvenaria estrutural de blocos de concreto. Foi empregado um hidroxipropil-metilcelulose (HPMC) em uma argamassa mista de cimento e cal, em diferentes teores (0,00%, 0,03%, 0,06% e 0,09% em relação à massa total de materiais secos) para a avaliação da influência do referido aditivo nas propriedades das argamassas no estado fresco e endurecido. Além disso, foram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…With all the questions exposed and the results obtained, it can be seen that the studied admixtures can have high retention depending on the chemical type used [13], [16], and they can have great variability of results between them, varying according to the chemical used and its characteristics.…”
Section: Figure 4 Water Retention Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With all the questions exposed and the results obtained, it can be seen that the studied admixtures can have high retention depending on the chemical type used [13], [16], and they can have great variability of results between them, varying according to the chemical used and its characteristics.…”
Section: Figure 4 Water Retention Resultsmentioning
confidence: 99%
“…On mixed mortars, the excessive water or trapped water can prevent CO2 from penetrating the mortar, slowing carbonation process [13]- [15]. Studies showed that the same type of cellulosic (HPMC) can present different percentages of water retention, according to the length of the molecular chain of the additive used and the dosage [16], [17]. This variation could reach up to 14% when comparing different types of cellulosic products [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mortar properties on fresh and hardened state directly influence the characteristics of the structural masonry joints, as well as the performance of the whole ensemble (Casali, 2008;Schankoski et al, 2015;Oliveira et al, 2015). The moment the mortar is placed in contact with the block, the processes of water removal and joint densification begin (Oliveira et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The mortar properties on fresh and hardened state directly influence the characteristics of the structural masonry joints, as well as the performance of the whole ensemble (Casali, 2008;Schankoski et al, 2015;Oliveira et al, 2015). The moment the mortar is placed in contact with the block, the processes of water removal and joint densification begin (Oliveira et al, 2015). The water transfer mechanism can result in two distinctive products, densification with a reduction in porosity and an increase in resistance or desiccation with an increase in porosity and a decrease in resistance (Casali, 2008).…”
Section: Introductionmentioning
confidence: 99%